2013
DOI: 10.1001/jamaophthalmol.2013.4694
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Disparity in Use of Eye Care Services Among US Adults With Age-Related Eye Diseases

Abstract: Individuals with age-related eye disease (ARED) need to use eye care services for detection, assessment, and care at regular intervals. OBJECTIVE To explore the association between socioeconomic position (SEP) and use of eye care services among US adults with self-reported ARED during 2002 and 2008. DESIGN Data were from the National Health Interview Survey 2002 and 2008. We used multiple logistic regression to estimate predictive margins, controlling for other factors, and we used the slope index of inequalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 38 publications
(30 reference statements)
3
50
3
Order By: Relevance
“…As the study was done in 3 clinics in 2 clinical practice settings in the mid-Atlantic region, it may not be representative of the entire United States, but we observe that the diversity in practice location provides a patient population from urban, suburban, and rural areas. Whereas study respondents had a higher level of education 19 and were more likely to be African American than the United States glaucoma pop- ulation, 20 neither race nor education was a significant predictor of cost in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…As the study was done in 3 clinics in 2 clinical practice settings in the mid-Atlantic region, it may not be representative of the entire United States, but we observe that the diversity in practice location provides a patient population from urban, suburban, and rural areas. Whereas study respondents had a higher level of education 19 and were more likely to be African American than the United States glaucoma pop- ulation, 20 neither race nor education was a significant predictor of cost in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…Even in the United States, annual use of eye services was significantly associated with levels of educational attainment after adjusting for other factors. [32][33][34] A randomized controlled trial demonstrated that educational interventions can successfully increase the uptake of cataract surgery. 35 Sex differences in the health burden of cataract vision loss were significant for each age group.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, men, those who are living alone, persons with lower socioeeconomic position and without current employment experienced the strongest decline. These findings are worrisome, given the fact that men and individuals with lower educational attainment, fewer financial resources and without a job also showed a steeper increase of type 2 diabetes over past two decades in Germany [1], have a higher risk of diabetes-related sequels [45,46], and lower quality of diabetes management [44,47]. Diabetes-related eye disease is particularly problematic in those with undiagnosed diabetes and the problem of underdiagnosis is greater within socioeconomically deprived subjects [48].…”
Section: Discussionmentioning
confidence: 99%